SARS-CoV-2 Infection-Associated Aortic Thrombosis Treated with Oral Factor Xa Inhibition - Strýčková, Alena; Benko, Jakub; Péč, Martin Jozef; Péčová, Monika; Žolková, Jana; Brunclíková, Monika; Bolek, Tomáš; Staško, Ján; Samoš, Matej; Mokáň, Marián (Case Reports in Hematology, 2022)
Coronavirus disease 2019 (COVID-19) is an acute complex systemic disorder caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2).While SARS-CoV-2 is known to cause significant pulmonary disease, various extrapulmonary manifestations of COVID-19 have also been reported. Growing evidence suggests that COVID-19 is associated with coagulopathy leading to micro and macrovascular complications. Although in patients with COVID-19, venous thromboembolic events are more frequent, arterial thrombosis also occurs at an increased rate. These often lead to acute life-threatening ischemia, which requires urgent diagnosis and treatment. We present case reports of two patients with an abnormal thrombus formation in the thoracic aorta who recently overcame COVID-19, which led to systemic embolism and splenic infarction. Ambulatory oral factor Xa inhibitor therapy led to aortic thrombosis resolution in both patients.